Visualisasi I Gusti Ngurah Made Agung dalam Geguritan Bhuwana Winasa dan Geguritan Puputan Badung - I Wayan Juliana (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2022)
Abstract             The war of Puputan Badung was one of the Balinese’s heroic stories in defending the unity of state. The war of Puputan Badung had born I Gusti Ngurah Made Agung as the leader in war against Dutch. Besides as the king and the leader of war, he was also the poet who had written many literary works such geguritan and kakawin. Although he had been pressured by Dutchman, he was able to think creatively in writing his works.             Based on his loyalty and dedication, this paper will identify his actualization as the king, the poet, and the leader of war which were described in the literary works. His characters were described in geguritan Bhuwana Winasa written by Ida Pedanda Ngurah and geguritan Puputan Badung (Bandana Pralaya) written by A.A Alit Konta. In this paper, the analysis will focus on the physical, the social, and the psychological aspects of I Gusti Ngurah Made Agung in geguritan Bhuwana Winasa and geguritan Puputan Badung.